2018
DOI: 10.1007/s00264-018-3819-9
|View full text |Cite
|
Sign up to set email alerts
|

A prospective comparative study of hip resurfacing arthroplasty and large-diameter head metal-on-metal total hip arthroplasty in younger patients—a minimum of five year follow-up

Abstract: Comparison of HRA and LDH MoM THA shows similar mid-term clinical results. HRA may be preferable due to the well-preserved bone stock and restoration of the native anatomy. LDH MoM THA may be used with caution due to the excessive metal ion release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Peri-operative parameters showed a tendency to favor THA over RHA in some studies. In fact, significantly lower operative time was reported in four series of patients [ 25 , 26 , 27 , 28 ] and significantly shorter incision length in two series of patients [ 25 , 29 ] in favor of THA. No paper found a statistically significant difference in terms of blood loss, even if a trend of lower values in RHA was reported in three series of patients [ 25 , 26 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peri-operative parameters showed a tendency to favor THA over RHA in some studies. In fact, significantly lower operative time was reported in four series of patients [ 25 , 26 , 27 , 28 ] and significantly shorter incision length in two series of patients [ 25 , 29 ] in favor of THA. No paper found a statistically significant difference in terms of blood loss, even if a trend of lower values in RHA was reported in three series of patients [ 25 , 26 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“… Correspondence between the 18 articles retrieved and the 9 series of patients treated [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. …”
Section: Figurementioning
confidence: 99%
“…37 Patient-related risk factors must be evaluated and considered preoperatively, intraoperatively and postoperatively. 9 There is evidence that age is an independent risk factor for dislocation but evidence of this is still controversial. 38 Advanced age (>75 years) is related to decline in muscular tone, inability to follow postoperative protocols and higher incidence of cognitive problems which have been linked to increased dislocation rates.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] In LDH MoM THAs, hip dislocation rates have been found to be very low (< 1%) or even non-existent. 1,9…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, total hip resurfacing arthroplasty (THRA) has been developed for younger and more active patients, especially for proximal femoral bone stock preservation [5]. It has the advantage of preserving the bone stock and restoration of the native anatomy [6]. However, several studies have shown that early postoperative femoral neck fracture occurred and was related to improper surgical operations and femoral prosthesis implantations which influenced the biomechanic characteristic of the hip [7,8].…”
Section: Introductionmentioning
confidence: 99%